PENERAPAN MODEL PETA PIKIRAN MENGGUNAKAN MEDIA CANVA DALAM PEMBELAJARAN MENULIS TEKS BIOGRAFI PADA SISWA KELAS X SMK PELITA JATIBARANG TAHUN AJARAN 2024/2025 - Nurul Aifah, Arneta; Zain Naufal, Muji; Unes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research on the application of the mind mapping model using Canva media in learning to write biographical texts for class X students of SMK Pelita Jatibarang in the 2024/2025 academic year aims to determine the results and process of learning activities in writing biographical texts. This study used two groups (experimental and control) which were conducted twice in each class to obtain pretest (before treatment) and posttest (after treatment) data. The pretest was given to determine students' knowledge and skills in learning to write biographical texts. Then the posttest was given to determine the effectiveness of using the mind mapping model using Canva media and its differences with the problem-based learning model using Vista Create media. In addition, observations will be carried out during the learning process to determine student activities during the learning. The results of student activities in learning in the experimental and control classes have differences in the average and criteria. In the experimental class, the average score was 46% with a very good category. While in the control class, the average value was 10% with a sufficient category. This can be concluded that the activity of students in the experimental class was higher than the control class. The difference in biographical text writing skills between the experimental class and the control class was shown by the results of the Wilcoxon and Mann Whitney statistical analysis tests. The results of the Wilcoxon and Mann Whitney nonparametric tests on the post-test scores of the experimental class and the control class both showed a significance value of Asymp.Sig.(2-tailed) = <0.05. from both results it can be concluded that there is an influence. So the mind map learning model using Canva media is an effective learning strategy.